Everyday Racism and Racialized Experiences Among Indonesian Migrant Muslims in New York City: Perception, Resistance, and Self-Empowerment - Irawaty, Diah (Jurnal Masyarakat dan Budaya, 2019)
The election of Donald Trump as the 45th President of the United States of America increased public conversations about the situations of immigrants living in the country. Trump employed the issue of immigrants as a powerful weapon to win the presidential race. In my view, the way the American people excitedly responded to and accepted Trump?s ideas indicates how racism against immigrants still plays a pivotal role in the US political and social realms. My reflection on this hot issue on immigration led me to wonder about some of my colleagues and friends from Indonesia who migrated to the US. How are they? Are they in a good situation?